PENGARUH ABU SEKAM PADI DAN COUPLING AGENT TERHADAP KETAHANAN USANG VULKANISAT BANTALAN DERMAGA - Marlina, Popy; Prasetya, Hari Adi (Jurnal Dinamika Penelitian Industri, 2017)
The research aimed to study the ageing resistance of vulcanized dock vendor with rice husk ash filler and coupling agent. The experimental research used non Factorial Completely Randomized Design and each treatments was replicated three times. Single factor concentration of ratio of rice husk ash and coupling agent 3-methacryloxypropyl trimethoxysilane (MPS) (70 phr: 1 phr, 100 phr: 1 phr, 130 phr: 1 phr, 160 phr: 1 phr, 190 phr: 1 phr and 220 phr : 1 phr). The parameters were hardness, tensile strength, elongation at break and ageing resitance before and after ageing. The results showed that all treatments have a influence on vulcanized dock fendor and meet the quality requirements SNI 06-3568-2006 for treatment concentration of ASP70 tol ASP160 with characteristics hardness of 70 Shore A, 75 Shore A, 78 Shore A dan 80 Shore A after ageing 68 Shore A, 72 Shore A, 76 Shore A dan 78 Shore A. The tensile strength before (19 N / mm2, 21 N / mm2, 17 N / mm2 and 16 N / mm2), after ageing (17 N / mm2, 20 N / mm2, 15 N / mm2 and 15 N / mm2). ASP70 to ASP220 treatment concentration up to the elongation at break before (350%, 345%, 330%, 220%, 209% and 200%), after ageing (343%, 335%, 325%, 216% and 200%). Tear resistance characteristics before (15.6 kg / cm, 17.2 kg / cm, 17.9 kg / cm, 18.2 kg / cm, 19 kg / cm and 20 kg / cm), after ageing (15 kg / cm, 16.1 kg / cm, 17.5 kg / cm, 17.9 kg / cm, 18.7 kg / cm.